A Classroom Transition to Electronic Learning: Improving EFL in Higher Education - Asti Gumartifa (Institut Agama Islam Negeri Palopo, 2021)
Electronic media are used to hold teachers in contact, give lots of links interaction to students, and deliver educational content services. Online learning education can eventually become the primary way in supporting the educational enrichment process. Their much effort is being put into the work practices and communication for both students and teachers that focused on enhancing the effectiveness of the study. This study gives additional future development of online learning that must follow the progress of the Internet as the modern technologies. Furthermore, it also explains some advantages and disadvantages of implementing Electronic learning during long-distance learning. Institutions need to use digital information technology for learning and teaching. This study examines relevant literature and enhances academic education by evaluating some of the achievements made by different researchers in the e-learning context, in particular the strengths and weaknesses of electronic learning in higher education. Finally, this study gives suggestions for future learners and teachers that electronic learning can be used for distance learning based on the learning purpose. Further, electronic learning basically can be used to enhance learners’ academic information. On the other side, communication between learners and teachers during the learning process is limited. Then, the impact of closeness between teacher and student decreases